P36 Loneliness, social isolation and health: 'What's the problem represented to be?' in the United Kingdom?. (13th September 2016) - Valtorta, NK; Hanratty, B
Abstract : Background: Loneliness, understood as the negative feeling experienced by those who perceive their social relationships to be deficient, and social isolation, characterised by the relative absence of contact with others, have recently been identified as a public health challenge in the United Kingdom. How is this social «problem» defined, who is expected to tackle it, and how? These are the questions we explore in our presentation. Methods: We used Bacchi's (2009) 'What's the problem represented to be?' framework, informed by Foucault's theory of governmentality and methods of problematization, archaeology and genealogy, to analyse the way in which the issue of loneliness and social isolation is represented in British policy. Taking the 2012 White Paper « Caring for our Future: Reforming care and support » as our starting point, we used discourse analysis to identify the assumptions of the public health strategy currently being promoted. Results: We identified three main assumptions: 1) being lonely or socially isolated is perceived to be particularly problematic in older age; 2) loneliness and social isolation are targeted as factors whose potential effects on health can be modified; 3) the involvement of civil society is identified as key to the delivery of interventions aimed at strengthening the social relationships of isolated individuals. We show how these assumptions shape the prevention strategies currently promoted, and what they omit. In particular, we discuss how the current focus on secondary and tertiary prevention ignores important dynamics such as lifecourse trajectories and social determinants of health. Conclusion: Actively questioning the representation of the «problem» of loneliness and social isolation in British policy allows us to shed light on the limitations of the intervention approach currently pursued. In particular, it highlights the absence of primary intervention initiatives, which are key to an effect prevention strategy.